The Role of Holistic Exegesis in Assuring Quality in Multimodal Translation - Harmelink M., Bryan L. (2025)
The seminal work of Kress and van Leeuwen in multimodality and social semiotics has inspired many other studies, including work in translation studies such as Translation and Multimodality: Beyond Words (Boria et al. 2020) and Multimodal Pragmatics and Translation (Dicerto 2017). The first part of this paper considers multimodality in relation to how it impacts our understanding of language and communication. The remainder of the paper explores implications of multimodality for exegesis, translation, and quality-assurance processes in Bible translation. Throughout the paper, experiences in multimodal or oral Bible translation will be discussed as practical examples of these implications.
Keywords: oral Bible translation; Exegesis; Translation; Multimodality